Plant Hormones - Recent Advances, New Perspectives and Applications 2022
DOI: 10.5772/intechopen.102689
|View full text |Cite
|
Sign up to set email alerts
|

Plant Hormones: Role in Alleviating Biotic Stress

Abstract: Plant hormones play a critical role in regulating plant developmental processes. Jasmonic acid, salicylic acid and brassinosteroids have been recently added to the list of plant hormones apart from auxins, gibberellins, cytokinins, abscisic acid and volatile hormone ethylene. Besides their regulatory role in plant development, plant hormones, ethylene, Jasmonic acid and salicylic acid play key roles in the plant defense response while as auxins, gibberellins, abscisic acid, cytokinins and brassinosteroids are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 225 publications
0
4
0
Order By: Relevance
“…In contrast to abiotic stress, the accumulation of ABA during biotic stress can either increase plant tolerance or susceptibility (Gietler et al 2020 ). The impact of ABA on plants is also influenced by pathogen type and biotic stress conditions (Bharath et al 2021 ; Rasool 2022 ). High levels of cellular ABA can suppress the immune response of crop plants by repressing salicylic acid activity, making them more susceptible to biotrophic pathogens, such as Magnaporthe oryzae (in barley) and Botrytis cinerea (in tomato), which infect living host cells (Ulferts et al 2015 ; Sivakumaran et al 2016 ).…”
Section: Abscisic Acid As a Hormonal Biomarker In Plant Stress Responsesmentioning
confidence: 99%
“…In contrast to abiotic stress, the accumulation of ABA during biotic stress can either increase plant tolerance or susceptibility (Gietler et al 2020 ). The impact of ABA on plants is also influenced by pathogen type and biotic stress conditions (Bharath et al 2021 ; Rasool 2022 ). High levels of cellular ABA can suppress the immune response of crop plants by repressing salicylic acid activity, making them more susceptible to biotrophic pathogens, such as Magnaporthe oryzae (in barley) and Botrytis cinerea (in tomato), which infect living host cells (Ulferts et al 2015 ; Sivakumaran et al 2016 ).…”
Section: Abscisic Acid As a Hormonal Biomarker In Plant Stress Responsesmentioning
confidence: 99%
“…Later, research revealed that it may have a part in plant development and plant stress adaptation [13]. ABA is produced in plastids through the methylerythritol phosphate route from carotenoids, a derivative of isopentenyl diphosphate [14][15][16][17]. ABA, often referred to as the "stress hormone," plays a crucial role in regulating multiple processes that enhance a plant's ability to withstand stress.…”
Section: Aba Mechanisms and Functionmentioning
confidence: 99%
“…Plant hormones or phytohormones are biochemicals required for the normal growth and development of plants [1][2][3]. Plant hormones include auxins (IAA), gibberellins (GAs) cytokinins (CK), abscisic acid (ABA), ethylene (ET), besides jasmonates (JA), salicylic acid (SA), brassinosteroids (BR), strigolactones (SL), and nitric oxide (NO).…”
Section: Introductionmentioning
confidence: 99%
“…and abiotic (drought, heat, salinity, heavy metals, etc.) stress [3][4][5][6]. Hormones act at the site of their biosynthesis or some distance away from it [3,[6][7][8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation